Circulating adipocyte fatty acid‐binding protein induces insulin resistance in mice in vivo. (10th April 2015) - Kralisch, Susan; Klöting, Nora; Ebert, Thomas; Kern, Matthias; Hoffmann, Annett; Krause, Kerstin; Jessnitzer, Beate; Lossner, Ulrike; Sommerer, Ines; Stumvoll, Michael; Fasshauer, Mathias
<x xml:space="preserve">Abstract</x> Objective Circulating levels of the adipokine adipocyte fatty acid‐binding protein (AFABP) are increased in obesity. However, the influence of circulating AFABP on insulin sensitivity in vivo remains unclear. Methods C57BL/6NTac mice (10 weeks) were treated over 8 weeks i.p. with saline (control) or recombinant AFABP (0.5 mg/kg/d). A comprehensive characterization of metabolic parameters, body composition, and energy expenditure was performed. Furthermore, the effect of AFABP on pancreatic β‐cell responsiveness, hepatic glycogen content, and peroxisome proliferator‐activated receptor (PPAR) γ protein expression was elucidated. Results In male mice, AFABP treatment induced insulin resistance with significantly increased fasting insulin, C‐peptide, and homeostasis model assessment of insulin resistance. In female animals, a similar trend was observed. In both genders, no difference in body weight, lipid parameters, body composition, or energy expenditure could be detected between AFABP‐treated and control mice. Insulin resistance in male AFABP‐treated mice was accompanied by decreased PPARγ protein content in perigonadal adipose tissue and diminished circulating adiponectin. AFABP treatment did not affect pancreatic β‐cell responsiveness and hepatic glycogen content. Conclusions Circulating AFABP induces insulin resistance in male mice. AFABP‐mediated degradation of PPARγ in adipose tissue and subsequently decreased expression of insulin‐sensitizing adiponectin are potential mechanisms for this effect.